Postbiotic metabolites present in the supernatants of Lysinibacillus xylanilyticus and Bacillus cereus promote the germination and growth of Hibiscus sabdariffa and Prosopis juliflora - Ruiz-Aymá, Gabriel; Romero-Arguelles, Ricardo; Rios-Del Toro, Esther E.; Juarez-Gaspar, Alexa; Olalla-Kerstupp, Alina; Loredo-Tovias, Marco; González-Rojas, José I.; Villarreal-Treviño, Licet; Guzmán-Velasco, Antonio; Gomez-Govea, Mayra A. (Frontiers in Microbiology, 2026)
IntroductionThe search for sustainable agricultural strategies has highlighted the importance of plant-microbe interactions within soil ecosystems. In particular, extracellular metabolites produced by soil bacteria represent a promising, yet underexplored, source of bioactive compounds capable of modulating plant germination and early development.MethodsThis study evaluated the biostimulant potential of extracellular metabolites present in bacterial cell-free supernatants on the germination and early growth of Hibiscus sabdariffa and Prosopis juliflora under controlled laboratory conditions. Two native bacterial strains isolated from soils of Nuevo León, Mexico, were identified as Lysinibacillus xylanilyticus and Bacillus cereus using MALDI-TOF mass spectrometry. Supernatants obtained after cultivation in Luria–Bertani (LB) medium were applied directly to seeds, and germination and growth parameters were recorded. Phytochemical screening of the supernatants was also performed.ResultsThe L. xylanilyticus supernatant significantly enhanced seed germination (96.66 ± 5.77%; p < 0.0001) and promoted early growth in both plant species, increasing shoot length, leaf width, and fresh biomass. In contrast, the B. cereus supernatant inhibited H. sabdariffa germination (30 ± 10%; p = 0.0146) and showed limited effects on P. juliflora. Notably, a 50:50 mixture of both supernatants completely inhibited H. sabdariffa germination while significantly stimulating P. juliflora germination (90 ± 10%; p = 0.0130). Phytochemical analysis revealed low concentrations of carbohydrates and coumarins, suggesting that the observed effects were likely mediated by other, unidentified bioactive metabolites.DiscussionThese findings demonstrate that extracellular metabolites produced by soil-derived bacteria exert species-specific and measurable biological effects on seed germination and early plant growth. The contrasting responses observed between plant species and supernatant combinations underscore the complexity of plant–microbe chemical interactions. Overall, this study highlights the potential of bacterial extracellular metabolites as microbiome-based tools for sustainable agriculture and ecological restoration.